Desigualdade e competição: duas faces da governamentalidade neoliberal - Malina, Pedro (2021)
This thesis is about the relationship between neoliberal governmentality, inequality, and competition. Starting on Michel Foucault’s concept of governmentality, this thesis seeks to understand how neoliberal governmentality works, having inequality as a general guide, understood as something not just economical, but as an important part of neoliberal functioning. Competition is one of the most important elements in neoliberal governmentality, since it is the idea of “free competition” between Market agents that serves as basis to society as a whole. Extrapolating economy to many areas of life, this governmentality also brings competition and inequality to these areas. To comprehend the relationship between neoliberal governmentality, inequality and competition, this work deals with neoliberal subjectivity, understood as a productive engine in this governmentality; the network diagram, as a format that potentializes power circulation in neoliberalism; how democracy is affected by inequality and the political affinity between neoliberalism and conservatism. Besides, some resistances in this power structure will also be analyzed, understanding that where there is power, there is also resistance